Investigating the Relative Contributions of Computerised Working Memory Training and English Language Teaching to Cognitive and Foreign Language Development. Issue 2 (12th October 2015) - Hayashi, Yuko; Kobayashi, Taisei; Toyoshige, Tsuyoshi
Summary: The current study reports on an intervention study that investigated the relative contributions of 5‐week English language training (ELT) and 5‐week working memory training (WMT) to improvements in English language knowledge and working memory capacity in university learners of English as a foreign language. The participants were allocated to one of the following three experimental groups and a control group: (i) ELT only; (ii) WMT only; and (iii) both WMT and ELT. The results showed that intervention effects were pronounced in the WMT + ELT group, who improved scores on the reading span test and all tests of verbal and visuo‐spatial short‐term and working memory. The gains on verbal short‐term (Japanese) and working memory (Japanese and English) were maintained 3 months later. None of the interventions, single or combined, were associated with gains in foreign language knowledge, however. The sustained effects of the dual approach and its implications are discussed. Copyright © 2015 John Wiley & Sons, Ltd.